Lead in street-vended grilled chicken innards a preliminary risk assessment - Palacio, Glorissa Cabuhat (2003)
ABSTRACT Grilled chicken innards have become a popular food item that is convenient to purchase at a relatively low price. There are possible risks related to consumption of these food items. These risks can be chemical, biological or physical in nature. This study looked into a possible chemical risk, specifically lead exposure. To estimate risk, two sets of data are vital-the occurrence data and the consumption data. Raw, processed and cooked chicken intestine and gizzard were analyzed for lead content using Flame Atomic Absorption Spectrophotometry; the values gathered from which are considered the occurrence data. Two hundred respondents were surveyed about the frequency and volume of consumption of these food items; the information gathered in the consumption survey constitute the consumption data. Using the two sets of data in a relatively simple equation, individual weekly lead intake was calculated. The computed intake was compared to the Potential Tolerable Weekly Intake (PTWI) set by WHO. Out of the two hundred respondents, eight exceeded the PTWI of 25μg lead/kg bodyweight/week. The highest intake amounted to 101μg lead/kg bodyweight/week. There may be no alarming risk involved in the consumption of these food items since only 4% of the respondents exceeded the PTWI but lead is a cumulative poison. Prolonged small intakes may also lead to chronic poisoning. Moreover, lead from other sources was excluded in this study. Their inclusion would absolutely increase lead intake.